Meningkatkan Kemapuan Hafalan Al Qur’an dengan Metode Kauny Quantum Memory pada Murid Disabilitas Intelektual Ringan - Nisrina Hudayani; Johandri Taufan; Damri; Yosa Yulia Nasri (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The ability to memorize the Qur'an in children with mild intellectual disabilities faces obstacles in the aspects of memory, concentration, fluency, and accuracy of reading. This study aims to improve the ability to memorize the Qur'an through the application of the Kauny Quantum Memory method. The study used a quantitative approach with the Single Subject Research (SSR) method and an A–B design, consisting of 5 baseline sessions (A) and 8 intervention sessions (B). Data were collected through memorization ability tests covering aspects of memory, reading fluency, reading accuracy, and consistency of memorization. Data analysis was carried out visually by paying attention to the trend of direction and stability of the data in each phase. The results showed an increase in all aspects of memorization ability, namely memory by 75%, reading accuracy by 75%, reading fluency by 68.7%, and memorization consistency by 75%. The change in direction and better level of ability in the intervention phase compared to the baseline phase indicate that the application of the Kauny Quantum Memory method contributed to the improvement of the ability to memorize the Qur'an in the study subjects. These findings suggest that the method could be an alternative approach to learning to memorize the Qur'an for children with mild intellectual disabilities, although further research with broader subjects and research designs is needed to test the consistency of the findings